Daily field checking list by Walter Rosene, April 28, 1939 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Robert Walker, April 28, 1939. Also notes two young Great Horned Owl's had left the nest and were perched nearby and one young Great Horned Owl was still in the nest cavity. Plustek--flatbed